Exposure Levels of Adult Patients during Radiographic Examinations: Sinuses and Coastal Grill Cases at the Ngaoundere Regional Hospital, Cameroon. (30th April 2019) - Gnowe, Guiswe; Ekobena, Fouda H. P.; Mbo, Amvene J.; Neossi, Guena M.
Abstract : Background . The purpose of this study was to estimate the doses delivered to adult patients during explorations of the sinuses and coastal grill whose attention in dosimetric terms is neglected because of the low demand for diagnosis. But yet dosimetric values are very high. Materials and Methods . The present study was transversely descriptive and was conducted between April and July 2016. The data were collected on 50 adult patients of mass of 70±10kg at the Regional Hospital of Ngaoundere (HRN). The dose at the entrance of the patients' skin was evaluated through the theoretical methods derived from the Davies model according to the 75th percentile calculations. Results and Discussion . The entrance skin doses obtained in mGy were, respectively, of 7.2±0.2 for sinuses and 5.27±0.1 for coastal grill. The present study found many variations in doses during radiological investigations. These variations allowed us to understand that the notions of quality of the radiographic image, insurance, and quality control of the radiological equipment are tributary, abstract, and often theoretical because doses delivered are not sufficiently optimized. Conclusion . The dosimetric analysis remains very worrying because the various procedures show that an improvement of the practices especially with respect to the technical parameters and the protocols must be considered. Therefore a strengthening of radiological protection skills of radiological manipulators (continuing education and retraining) would contribute to a better protection of patients.